Characterization of TLR9 responsiveness in cell subsets derived from in vitro pDC differentiation of hematopoietic stem and progenitor cells - Sánchez Hernández, Sabina; Bjerg, Tobias Wang; Nielsen, Ian Helstrup; Laustsen, Anders; Q Tang, Hai; Pedersen, Lars Henning; Klechevsky, Eynav; Jakobsen, Martin R.; Bak, Rasmus O. (Frontiers in Immunology, 2025)
Plasmacytoid dendritic cells (pDCs) are multifunctional immune cells with roles in both the innate and adaptive immune system. Their hallmark function is production of large amounts of type I interferons in response to viral infections, but they are also capable of producing a range of other cytokines, antigen presentation, and cytotoxicity. Their potential as an immunotherapy for cancer and infectious disease is being explored, but broad application of these cells is challenged by low frequency in the blood and low viability during ex vivo culturing. We have previously developed an effective in vitro differentiation protocol for producing pDCs from CD34+ hematopoietic stem and progenitor cells (HSPC-pDCs), which provides an attainable and large source of pDCs. HSPC-pDCs present pDC characteristics and functions, and like naturally occurring pDCs they exhibit large phenotypic and functional heterogeneity. Here, we characterize different cell subsets from in vitro pDC differentiation and identify a distinct population, which is the major producer of IFNα in response to TLR9 stimulation and display a transcriptomic profile similar to what is seen for pDCs circulating in the blood. We also investigate the possibility of rerouting subset specification during HSPCs-to-pDC differentiation by controlling gene expression of key master transcription factors (TFs). We identify TFs associated with the pDC differentiation trajectory that are essential for the development of TLR9-responsive HSPC-pDCs, and we also identify TFs that increase their frequency. In conclusion, we phenotypically and functionally characterize different cell subsets and modulate their relative frequencies by manipulating TF expression during pDC differentiation. These findings provide a deeper understanding of in vitro-differentiated pDC cultures that may spur further developments in their use as an immunomodulatory cell therapy.